The Function Of Institutional Evaluation In the Quality Of Madrasah Aliyah Education In Indonesia - Khairiah Khairiah; Shafinar Ismail (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2023)
Abstract: Madrasah Aliyah in Indonesia is still difficult to achieve the quality of education, it is marked that there are still some teachers who have not met the minimum education qualification of S1 / D4, teachers teach not according to their field of expertise, there are still many Madrasah Aliyah with non-civil servant status. The general objective is not only to map the quality of Aliyah madrasah education, but also to evaluate institutional difficulties in achieving the quality of Aliyah madrasah education. Using descriptive qualitative methods to explore primary and secondary data sources. Secondary data from madrasah educational institutions. Primary data includes profiling, motivation, types of difficulties and institutional solutions to each difficulty in achieving the quality of madrasah Aliyah education. The results of the study can be concluded that the evaluation function in the quality of madrasah Aliyah education in Indonesia shows that; (1) there is still a gap between planning and program implementation, marked by the Aliyah madrasah has not been able to implement the planned program; (2) there is still a gap between the status of ability and the standards of the world of work, indicated by there are still teachers who are not able to work according to their field of expertise; and (3) there is still a gap in goals in madrasah educational institutions characterized by socioeconomic disparities in the community, thus affecting education equity, creating prolonged conflicts in society, making educational goals difficult to achieve. So it can be suggested that to achieve the quality of madrasah education, it improves the function of institutional evaluation among Aliyah madrasahs in Indonesia. Keywords: Function, Institutional Evaluation, Quality of Education, Madrasah Aliyah Indonesia Abstrak: Madrasah Aliyah di Indonesia masih kesulitan mencapai mutu pendidikan, ditandai masih terdapat sebagian guru belum memenuhi kualifkasi pendidikan minimal S1/D4, guru mengajar belum sesuai bidang keahliannya, masih banyak madrasah Aliyah berstatus non PNS. Tujuan umum selain untuk memetakan bentuk mutu pendidikan madrasah Aliyah, juga mengevaluasi kesulitan kelembagaan dalam mencapai mutu pendidikan madrasah Aliyah. Menggunakan metode kualitatif deskriptif untuk menggali sumber data primer dan sekunder. Data sekunder dari lembaga pendidikan madrasah. Data primer mencakup profiling, motivasi, tipe kesulitan dan solusi yang ditempuh kelembagaan atas setiap kesulitan dalam mencapai mutu pendidikan madrasah Aliyah. Hasil penelitian dapat disimpulkan bahwa fungsi evaluasi dalam mutu pendidikan madrasah Aliyah di Indonesia menunjukkan bahwa; (1) masih terdapat kesenjangan antara perencanaan dengan pelaksanaan program, ditandai dengan madrasah Aliyah belum mampu melaksanakan program yang telah direncanakan; (2) masih terdapat kesenjangan antara status kemampuan dengan standar dunia kerja, ditandai dengan masih terdapat guru belum mampu bekerja sesuai bidang keahliannya; dan (3) masih terdapat kesenjangan tujuan dalam lembaga pendidikan madrasah ditandai dengan kesenjangan sosial ekonomi masyarakat, sehingga mempengaruhi pemerataan pendidikan, menciptakan konflik berkepanjangan dalam masyarakat, sehingga tujuan pendidikan sulit tercapai. Sehingga dapat disarankan bahwa untuk mencapai mutu pendidikan madrasah, maka tingkatkan fungsi evaluasi kelembagaan di madrasah Aliyah. Kata Kunci: Fungsi, Evaluasi Kelembagaan, Mutu Pendidikan, Madrasah Aliyah Indonesia